Needs Analysis in Instructional Material Design: Job Sheets for English Language Teaching Practicum - Adi Fitra; Risda Asfina (Juliet, 2026)
English students, in the English Language Teaching (ELT) practicum course, need to enhance their teaching skills, classroom management, and self-reflection. They need the materials that improve their preparedness, autonomy, and confidence in conducting teaching practices. This whole study aims to develop job sheets as practice-oriented instructional materials to support the effectiveness of the English Language Teaching (ELT) practicum course that guide students in applying theoretical knowledge into real teaching contexts. The research applied a Research and Development (R&D) method using the ADDIE framework consisting of analysis, design, development, implementation, and evaluation stages. This current study focused on the first stage. The data were collected through questionnaires and interviews. The study took place at Politeknik Negeri Bengkalis, involving 25 students from the English Language study program, the head of the study program, and the head of the department. The findings indicate that ELT job sheets are highly needed to support English Language students’ learning during the practicum course, particularly in helping them understand course materials, integrate theoretical knowledge with teaching practice, and prepare for their future. The results also show that job sheets are expected to contribute to the development of essential competencies, including English proficiency, pedagogical skills, lesson planning ability, teaching confidence, and professional competence. In addition, institutional perspectives emphasized the importance of aligning instructional materials with curriculum objectives, graduate competencies, and current ELT developments. The study further highlights the need for well-structured ELT job sheets with clear learning objectives, understandable instructions, step-by-step activities, and sufficient practice tasks. Overall, this needs analysis provides a strong foundation for the subsequent design and development of ELT job sheets aimed at improving the effectiveness of ELT practicum course.